PERAN STRUKTUR MODAL DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL PENGARUH KEPEMILIKAN MANAJERIAL, KOMISARIS INDEPENDEN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KUALITAS LABA - Duma Rahel Situmorang (Universitas Methodist Indonesia, 2019)
The purpose of this study is to test and analyze the role of capital structure and company size as variable control of the influence of managerial ownership, independent commissioners, and institutional ownership on earnings quality. Earnings quality is measured by discretionary accruals using Modified Jones Model. This research uses secondary data that were taken from the manufacturing companies which are listed in Indonesia Stock Exchange. There are 66 manufacture companies selected as research samples on the period of 2013 until 2017 based on purposive sampling method. The analytical method for this research uses panel data regression with the aid of the Eviews program. The result shows that partially, managerial ownership, independent commissioner, and institutional ownership had a significant influence on the earnings quality. Capital structure is able as a good control variable, because capital structure had negative significant influence.